Further instances of functional anomaly of the spermathecal gland in Coleoptera (Staphylinidae Curculionidae Scolytidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
In some species of Coleoptera, females are used to store a large amount of sperm into their spermathecal gland. Previously, this functional anomaly of the gland was known only for a restrict number of Scolytidae and Curculionidae. New instances are presented in this paper; they refer to Dactylotrypes longicollis (Wollaston) (Scolytidae), Microlarinus lareynii (Jacquelin du Val) (Curculionidae-Cleoninae), Torneuma rosaliae Rottenberg (Curculionidae-Cryptorhynchinae), Pachytychius hordei squamosus (Gyllenhal) (Curculionidae-Curculioninae), Ocypus olens (O.F. Muller), Philonthus concinnus (Gravenhorst), P. debilis (Gravenhorst) e P. intermedius (Lacordaire) (Staphylinidae-Staphylininae).Iconography refers also to 4 species of Staphylinidae-Staphylininae, which don't exhibit the gland anomaly: Cafius xantholoma (Gravenhorst), Quedius scintillans (Gravenhorst), Gabronthus maritimus (Motschulsky) and Philonthus spinipes Sharp.Because such anomaly does recur in different families and superfamilies, it may be regarded as an instance of adaptive convergence. In author's view, the selection of the sperm acquired throughout multiple mating is the common reproductive featureof the involved females.
Keywords: receptacle; gand reservoir; adaptive convergence; sperm segregation